Tasting Tourism: Evaluating Gastro Offerings in Sarajevo and Mostar via TripAdvisor Reviews - Banda, Amra (Turizam, 2025)
Sarajevo and Mostar, the most visited destinations in Bosnia and Herzegovina (BiH), are well known for their gastronomic offerings. Influenced by diverse traditions and cultures, their culinary scenes reflect a notable influence of the Ottoman Empire. Both destinations boast numerous restaurants serving delicious dishes from both local and international cuisines. As online review platforms are a leading source of information in hospitality and tourism, this paper analyses TripAdvisor reviews of 56 restaurants in Sarajevo and 21 restaurants in Mostar that specialize in offering local cuisine. Given that traditional dishes have become a key factor in destination selection and tourist attraction, the aim of this study is to assess tourist satisfaction and highlight similarities and differences in perceptions of the local gastronomic offer in Sarajevo and Mostar. The research findings indicate that the most influential factor in tourist satisfaction is the balance between food quality and price. Interestingly, in both destinations, tourists perceive the local cuisine as Bosnian cuisine. The results of this analysis may serve as a valuable tool for policymakers and businesses to develop and effectively promote local gastronomic offerings.
Keywords: Sarajevo, Mostar, TripAdvisor, local cuisine, content analysis, reviews.